Development of A Learning Module Supported by Augmented Reality on Chemical Bonding Material to Improve Interest and Motivation of Students Learning for Senior High School - Achmad Saiful Whatoni; Hari Sutrisno (Jurnal Penelitian Pendidikan IPA, 2022)
The chemical bonding material is a concept that requires visualization. For students to comprehend chemical bonding concepts better, molecular forms must be depicted in the materials. Consequently, a learning module that can show 3D things made from molecular structures is necessary. This study aims to create and evaluate an augmented reality-based learning module on chemical bonds while examining the similarities and differences between students' interests and learning motivation before and after utilizing the augmented reality-based learning modules. The product is designed utilizing a 4-D model, and this study uses a research and development model. A quasi-experimental method and one group pretest and posttest design were used to evaluate the module involving 53 students chosen randomly. A sample of Hotelling's T2 test was used to analyze the student responses to the questionnaire about interest and motivation for learning. Descriptive quantitative analysis was used to analyze the data from the product quality assessment. The results showed that the developed augmented reality-supported chemical bonding learning module was very suited for chemistry learning and that there were variations between pre- and post-usage in student interest and motivation to study simultaneously or separately